2023
DOI: 10.1093/procel/pwad031
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome research outlook: past, present, and future

Abstract: With its critical role in human health and disease, the microbiome has transformed modern biology. Over the past few years, microbiome research has evolved rapidly, with microbiologists gradually shifting their focus from cataloging microorganisms in the human microbiome to understanding their functional roles and how they interact with the host. Here, we present the global trends in microbiome research and summarize the past and current work on microbiome published in Protein & Cell. In closing, we highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Notably, our findings align with prior research indicating a negative correlation between the abundance of Pseudomonas and sperm concentration, while simultaneously noting a direct correlation with the total number of motile sperms [2]. However, it is essential to acknowledge the limitations of 16S rDNA sequencing technology [23], which restrict our ability to precisely identify the bacterial strains responsible for AZS. Nevertheless, this aspect remains a focal point for future research.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, our findings align with prior research indicating a negative correlation between the abundance of Pseudomonas and sperm concentration, while simultaneously noting a direct correlation with the total number of motile sperms [2]. However, it is essential to acknowledge the limitations of 16S rDNA sequencing technology [23], which restrict our ability to precisely identify the bacterial strains responsible for AZS. Nevertheless, this aspect remains a focal point for future research.…”
Section: Discussionsupporting
confidence: 84%
“…We are aware that microbiome research has evolved enormously since then, moving from describing microorganisms belonging to the human microbiota to elucidating their functional roles and their highly personalized interactions with the host [ 73 ]. Technical improvements, from sequencing technologies, and culturomics to transcriptomics, metabolomics, and bioinformatics, have revolutionized the workflow of microbiome research, facilitating extensive study of the functions and mechanisms of the microbiome [ 74 ]. Such approaches can be applied nowadays to samples obtained in clinical trials, enabling a better knowledge about the mechanisms of action of a given strain and why the health outcomes may be different depending on the host, opening the possibility of future personalized interventions [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a study from Gao et al [ 4 ] found that the more relevant studies cover six important aspects of microbiome research. They include best practices for analyzing microbiomes, the regulation of gut microbiomes in the human immune system, how microbiomes affect immune sensing, the role of microbiomes in the gut-brain interaction, the application of microbiomes in maternal and newborn health, and the study of nutri-microbiome epidemiology.…”
Section: Introductionmentioning
confidence: 99%